Occurrence of Local Tsunamis Along the Eastern Coast of the Korean Peninsula Based on Numerical Modeling of Historical Earthquakes - Ha, Taemin; Yoon, Jae-Seon; Kyung, Jai Bok; Yoon, Seok-Hoon; Lee, Dong-Woo; Kim, Kwang-Hee (Frontiers in Earth Science, 2022)
Korean historical literature records a major offshore earthquake with an associated tsunami in the East Sea of Korea in 1681. The event also generated strong ground motion and landslides over the Korean Peninsula. This study examined the occurrence and characteristics of the reported tsunami along the eastern coast of the peninsula using numerical modeling of tsunami propagation from submarine faults identified in a recently compiled marine fault map. Results from some scenarios indicated runup heights in good agreement with descriptions in historical records. We also examined the time required for tsunamis to travel from the causative faults to vulnerable areas along the eastern coast under various scenarios. Our results successfully hindcast the occurrence and effects of local tsunamis in the historical literature and have important implications for assessing tsunami hazard and risk for coastal areas of the Korean Peninsula.